What Are Some Best Practices for Inspecting and Maintaining Fire Hydrants?. Issue 6 (1st June 2017) - ,
Abstract : The fire hydrant is one of the most visible, yet often overlooked, components of a water utility's distribution system—overlooked in the sense that it sits idle most of the time, is only occasionally inspected and tested, and yet is expected to perform flawlessly during an emergency.